Healthcare waste management in developing countries - M. Habibur Rahman; S. Mansoor Ali (2000)
This study presents a brief over view of the socioeconomic and health impacts of existing HCW management practices in developing countries in general with special emphasis on existing practices in Bangladesh. Information about existing HCW generation rates and their composition is also included. An attempt has been made to provide appropriate guidelines for potential practical solutions based upon the lessons learned from international case studies.